Comparative responses of two congeneric larval parasitoids of emerald ash borer to ambient temperatures: Implications for biocontrol introduction - Yingqiao Dang; Mitchell A. Green; Xiaoyi Wang; Jian J. Duan (Biological Control)
Understanding how climate influences the establishment of introduced species is critical to classical biological control programs against insect pests. Even closely related species with similar life histories may establish and perform differently in new environments due to different responses to ambient temperature. Here we compared the host attack rate and immature development of two congeneric larval parasitoids of emerald ash borer (EAB) Agrilus planipennis Fairmaire, Spathius agrili Yang and S. galinae Belokobylskij and Strazenac, under a range of temperatures from 17.2 to 32.8 ℃. We found significant differences between the two parasitoids in host attack rates and progeny development. Spathius agrili could parasitize EAB larvae across the temperature range of 17.2 ℃ to 32.8 ℃ and caused the highest parasitism rate (∼90.0 %) at 28.9 ℃. In contrast, S. galinae did not attack any host larvae at 32.8 ℃ and caused the highest parasitism rate (∼92 %) at 25 ℃. From 21.1 ℃ to 28.9 ℃, S. agrili emerged on average nine days earlier than S. galinae and had a higher low-temperature threshold for development. Both species arrested their development as mature (5th) instars inside their cocoons at 17.2 ℃, suggesting facultative diapause that may be induced by exposure to cool temperatures. These findings suggest that S. agrili may perform better in warmer climates than S. galinae and could be an effective biocontrol agent in the southern U.S., whereas S. galinae is better suited to be released in the northern U.S.